Adsorptive Removal of Arsenic (III) from Aqueous Solution Using Chemically-Modified Sweet Lime (Citrus limetta) Peels - Karki, Subarna; Aryal, Ram Lochan; Bhattarai, Sitaram; Gautam, Surendra Kumar; Poudel, Bhoj Raj (Journal of Nepal Chemical Society, 2017)
available with fulltext